Evaluasi Program Akselerasi di SMA Negeri 3 Kota Gorontalo - Zelan Tamrin Danial (IAIN Manado, 2021)
Evaluation of the Acceleration Program in SMA Negeri 3, Gorontalo. This study aims to: a) evaluate various policies regarding the acceleration program in SMA Negeri 3 Gorontalo city at the context stage, b) evaluate the availability of available resources to support the implementation of the acceleration program in SMA Negeri 3 Gorontalo city at the input stage, c) evaluate the implementation of the acceleration program at SMA Negeri 3 Gorontalo city at the stage of the process, and d) evaluate the success achieved in the implementation of the acceleration program in SMA Negeri 3 Gorontalo city at the product stage. This study employs an evaluative approach with data collection techniques, such as interview, observation and documentation.The results indicate that; 1) the results of the evaluation context that supports the acceleration program at SMA Negeri 3 Gorontalo city show that there is an acceleration program of policy in SMA Negeri 3 Gorontalo City and the understanding of policy makers about the acceleration program in SMA Negeri 3 Gorontalo city is intensively good , the formulation of the vision and mission of the school supports the policy implementation of the accelerated program, b) the results of the input evaluation show that the input component is a) the availability of human resources, namely teachers and academic support personnel, 2) the availability of facilities and infrastructure that support the implementation of the program (classes, laboratories, IT), d) curriculum, e) student recruitment , f) availability of funds, all of which support the acceleration program at SMA Negeri 3 Gorontalo city, 3) the results of the evaluation of the process show that the stages of the learning process carried out in the acceleration program in SMA Negeri 3 Gorontalo city are very dynamic and support the improvement of the competence of students studying in the accelerated class, and 4) the results of product evaluation indicate that a product stage of the acceleration program at SMA Negeri 3 Gorontalo city , shows that the evaluation criteria for students’ learning outcomes in the accelerated class display good results with an average of 95.75 or very good category.